2022
DOI: 10.1108/sasbe-10-2021-0185
|View full text |Cite
|
Sign up to set email alerts
|

The role of internet of things (IoT) in the assessment and communication of indoor environmental quality (IEQ) in buildings: a review

Abstract: PurposeThe changes brought by Industry 4.0 go beyond transformations in the industrial environment. The increasingly frequent digitization and robotization of activities is not only restricted to the industrial environment, but also to people's daily routine. People spend a large part of their time inside buildings, and maintaining adequate Indoor Environmental Quality (IEQ) is an essential factor for a healthy and productive environment. In this sense, the purpose of this study is to verify how the Internet o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 131 publications
(183 reference statements)
0
11
0
Order By: Relevance
“…The proposed framework can simultaneously minimize building energy consumption, life cycle costs, and environmental impacts. Similar research has been conducted by [14][15][16].…”
Section: Introductionmentioning
confidence: 52%
“…The proposed framework can simultaneously minimize building energy consumption, life cycle costs, and environmental impacts. Similar research has been conducted by [14][15][16].…”
Section: Introductionmentioning
confidence: 52%
“…Smell from clothing and lavatory), moisture and air temperature are critical to assessing indoor air quality. In a recent study, Goodarzi et al . (2023) reported that the choice of building materials and ventilation properties had a high impact on indoor air quality and energy consumption.…”
Section: Literature Reviewmentioning
confidence: 95%
“…Research and knowledge development and electronic automation are emerging as fundamental technologies and techniques for planning, operating, and constructing sustainable buildings. In this context, Broday and Gameiro da Silva [96] emphasize that Industry 4.0 has played a pivotal role in reshaping the built environment, mainly through the introduction of robotics and digitization to enhance building health. However, studies indicate a lack of research and profound understanding of the qualitative connections between Indoor Air Quality (IAQ), workplace performance or health, and their relationship with energy consumption and energy efficiency.…”
Section: Environmental Impact and Risk Assessment For Sustainable Bui...mentioning
confidence: 99%